2020
DOI: 10.1371/journal.pone.0226860
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary wheel running has no impact on brain and liver mitochondrial DNA copy number or mutation measures in the PolG mouse model of aging

Abstract: The mitochondrial theory of aging attributes much of the aging process to mitochondrial DNA damage. The polymerase gamma (PolG) mutant mouse was designed to evaluate this theory and thus carries a mutated proofreading region of polymerase gamma (D257A) that exclusively transcribes the mitochondrial genome. As a result, PolG D257A mice accumulate mitochondrial DNA (mtDNA) mutations that lead to premature aging, as evidenced by hair loss, weight loss, kyphosis, increased rates of apoptosis, organ damage, and an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Indeed, we detected a mutation frequency that was approximately 70 times higher in KO mtDNA compared to the nDNA, which is consistent with what is known about the mutation rates between the two. , Specifically, the point mutation, G→A, hypothesized through these analyses has been shown to be 70 times more prevalent in mtDNA than in nDNA in previous pyrosequencing studies in Drosophilia . The mutation frequency we calculated based on the LC-MS/MS results and compared to the known mtDNA base content is on the order of that detected in the POLG mutator mouse, a model known to accumulate mtDNA mutations due to the expression of deficient polymerase γ protein …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, we detected a mutation frequency that was approximately 70 times higher in KO mtDNA compared to the nDNA, which is consistent with what is known about the mutation rates between the two. , Specifically, the point mutation, G→A, hypothesized through these analyses has been shown to be 70 times more prevalent in mtDNA than in nDNA in previous pyrosequencing studies in Drosophilia . The mutation frequency we calculated based on the LC-MS/MS results and compared to the known mtDNA base content is on the order of that detected in the POLG mutator mouse, a model known to accumulate mtDNA mutations due to the expression of deficient polymerase γ protein …”
Section: Discussionsupporting
confidence: 86%
“…71 The mutation frequency we calculated based on the LC-MS/MS results and compared to the known mtDNA base content is on the order of that detected in the POLG mutator mouse, a model known to accumulate mtDNA mutations due to the expression of deficient polymerase γ protein. 63 The impact of Brca1 on the skeletal system is still a burgeoning and intense area of research. Brca1 has been shown to localize in both the nucleus and mitochondria, and its loss drastically impacts the musculature of an organism.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria, the powerhouses of the cell, have their own genomes. Multicopy mitochondrial DNA (mtDNA) genomes-e.g., present in thousands of copies in brain and skeletal muscle and in approximately 200,000 copies in mature oocytes [16][17][18][19][20]-are transmitted in mammals through the maternal lineage. Studying how mutations in mtDNA accumulate with age is critical because of their association with numerous human genetic diseases (reviewed in [21]) as well as with aging phenotypes [22], including Parkinson's and Alzheimer's diseases [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study reported that a POLG-mutant mouse carrying a D257A mutation in a key residue of mitochondrial DNA polymerase experienced a loss of mtDNA stability, leading to a significant acceleration of aging processes. 278,279 Moreover, increased mtDNA mutation burden contributes to abnormal mitochondrial biogenesis resulting in programmed cell death in cardiomyocytes 280,281 (Fig. 4).…”
Section: Mitochondrial Ros and Mtdnamentioning
confidence: 99%